1997
DOI: 10.1093/jee/90.6.1514
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 Field Insecticide Tolerance and Development of Laboratory Resistance in Grape Vine Populations of Drosophila melanogaster(Diptera: Drosophilidae)

Abstract: Studies were conducted between 1993 and 1996 using 3 natural grape vine populations, 1 susceptible laboratory strain, and 1 resistant selected strain of Drosophila melanogaster L. In vitro monooxygenase activity (ethoxycoumarine-O-deethylation) (ECOD) was recorded from microsomal fractions of all strains. Results varied over a 6-fold range between susceptible laboratory Canton and resistant selected RDDT strains and over a 2-fold range between the Canton strain and natural populations of flies. Few significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In insects, ECOD and GST activities have often served as convenient measures of overall phases I and II metabolizing enzyme activities. In addition, levels of ECOD and GST activities have been associated with sensitivity to insecticides [33], [34]. Our results showed that ECOD activity remained unchanged at 10 days p.i, in fat body and midgut whereas GST activity increased significantly in both tissues.…”
Section: Discussionmentioning
confidence: 50%
“…In insects, ECOD and GST activities have often served as convenient measures of overall phases I and II metabolizing enzyme activities. In addition, levels of ECOD and GST activities have been associated with sensitivity to insecticides [33], [34]. Our results showed that ECOD activity remained unchanged at 10 days p.i, in fat body and midgut whereas GST activity increased significantly in both tissues.…”
Section: Discussionmentioning
confidence: 50%
“…Increases in Cyp6a2 mRNA (and the resultant Cyp6a2 protein) have been associated with metabolic pesticide resistance both in terms of over‐transcription of this gene and in terms of changes in catalytic properties. Cyp6a2 expression levels in pesticide resistant and susceptible strains of Drosophila have been measured using western blots (Bride et al ., 1997) and a correlation was observed between Cyp6a2 titre and resistance (Bride et al ., 1997). However, Cyp6a2 expression level was not a predictor of resistance level.…”
Section: Discussionmentioning
confidence: 99%
“…The documentation of this phenomenon helps to explain the relatively high toxicity of fipronil and why, in numerous insect groups, fipronil typically retains its toxicity to populations which do not appear to be in possession of altered GABA‐gated chloride/ionopore target sites 2–4. 19, 20 The similar toxicity of fipronil and fipronil‐sulfone observed here also helps to explain the apparent lack of effects by PBO in bioassays (ie by inhibiting sulfone formation the net toxicity is not compromised). More general speculation of this relationship on a broad scale may be inappropriate at this time, but experimentation with a diverse array of insect groups would probably provide valuable information.…”
Section: Discussionmentioning
confidence: 99%